FROM THEORY TO PRACTICE: PEDAGOGICAL COMPETENCE TRANSFORMATION OF EFL PRE-SERVICE TEACHERS DURING TEYL PRACTICUM IN KINDERGARTENS - Henry Elisa; Yokie Prasetya Dharma; Tuti Tuti (STKIP Persada Khatulistiwa Sintang, 2026)
This study investigates the transformation of pedagogical competence among sixth-semester EFL pre-service teachers during a Teaching English to Young Learners (TEYL) practicum in kindergartens in Sintang. The study explores how sixth-semester English Language Education students from STKIP Persada Khatulistiwa navigate the shift from theoretical knowledge to real-life classroom practice in the even semester of Academic Year 2024/2025. Data were collected through reflective journals, semi-structured interviews, video recordings of teaching, and feedback from mentor teachers at partner kindergartens in Sintang. Using thematic analysis, findings reveal three key transformation stages: 1) Reality Shock confronting the gap between TEYL theories and under-resourced classrooms, 2) Contextual Adaptation developing strategies by integrating local culture, nature-based media, and children’s L1, and 3) Teacher Identity Formation shifting from “English instructor” to “facilitator of meaningful childhood experiences”. The study also identifies critical incidents that accelerate competence growth, including managing multilingual learners and teaching with technology. Implications suggest that TEYL practicum should be redesigned as a life-based experiential learning model rather than mere teaching drills. This research contributes to EFL teacher education discourse by linking pedagogical competence with social responsiveness.